Lara Croft, Tomb raider : the cradle of life [videorecording (DVD)] - Silvestri, Alan (Paramount, 2021)
Archaeologist and explorer extrodinaire Lara Croft journeys to a temple in Greece, sunken underwater, that leads to a sphere that contains the mythical Pandora's Box. A Chinese crime syndicate leader steals it. He's in league with a villain named Reiss who wants to use the Box as a doomsday weapon.